Whistleblowing and Internal Communication - Nan, Lin; Zheng, Ronghuo (The Accounting Review, 2026)
ABSTRACT We investigate how incentives provided by whistleblowing programs affect the likelihood of whistleblowing, firm value, and social welfare in the presence of endogenous internal communication. Specifically, we focus on a myopic manager’s ex post decision on internal communication with the employee. An informed employee plays a dual role: working to fix the defect internally or acting as a whistleblower to expose the misconduct if the manager withholds defect information from the public. We find that, when the whistleblowing reward is relatively small, providing stronger incentives increases the likelihood of whistleblowing and can help improve firm value and social welfare. However, once rewards become excessively large and compromise internal communication, contrary to conventional wisdom, the likelihood of whistleblowing declines and both firm value and social welfare decline too. We also characterize the optimal whistleblowing rewards designed by strategic regulators seeking to maximize firm value or social welfare. JEL Classifications: D83; G30; G34; M40.